Fines, Fees, Forfeitures, and Disparities: A Link Between Municipal Reliance on Fines and Racial Disparities in Policing. Issue 3 (7th August 2020) - Shoub, Kelsey; Christiani, Leah; Baumgartner, Frank R.; Epp, Derek A.; Roach, Kevin
Abstract : We investigate a possible linkage between municipal reliance on fines, fees, and forfeitures as a revenue source and policing behavior. With a dataset of four million traffic stops made by North Carolina municipalities, we demonstrate that a regular reliance on fines, fees, and forfeitures has powerful, predictable, and racially distinct impacts on black and white drivers, and that fiscal stress exacerbates these differences. A greater regular reliance on fines, fees, and forfeitures is linked to a decrease in the probability of white, but not black, drivers being searched; and increased odds of finding contraband among those white drivers who are searched, but no such change for black drivers. We validate the North Carolina tests with aggregate analyses of municipalities across four states. Abstract : 我们调查了自治市对罚款、罚金、没收物作为收入来源的依赖与治安行为之间可能的联系。利用北卡罗来纳州自治市提供的4百万次交通拦检数据集，我们证明，对罚款、罚金、没收物的定期依赖对黑人和白人驾驶员产生了强有力的、可预期的、种族差异明显的影响，并且财政压力加剧了这些差异。对罚款、罚金、没收物的定期依赖增加与以下因素相关：白人驾驶员被搜查的可能性降低，而不是黑人；从被搜查的白人驾驶员处发现违禁品的机率增加，但黑人驾驶员则没有出现这样的变化。我们对四个州的自治市进行综合分析，证实了北卡罗来纳州的测试。 Abstract : Investigamos un posible vínculo entre la dependencia municipal de multas, tarifas y decomisos como fuente de ingresos y comportamiento policial. Con un conjunto de datos de cuatro millones de paradas de tráfico realizadas por los municipios de Carolina del Norte, demostramos que una dependencia regular de multas, tarifas y decomisos tiene impactos poderosos, predecibles y racialmente distintos en los conductores blancos y negros, y que el estrés fiscal exacerba estas diferencias. Una mayor dependencia regular de multas, tarifas y decomisos está relacionada con: una disminución en la probabilidad de que se busquen conductores blancos, pero no negros; y mayores probabilidades de encontrar contrabando entre los conductores blancos que son buscados, pero no existe tal cambio para los conductores negros. Validamos las pruebas de Carolina del Norte con análisis agregados de municipios en cuatro estados.